Simple and elegant design of a virion egress structure in Archaea - Quax, Tessa E. F. (National Academy of Sciences, 2011)
Some viruses of Archaea use an unusual egress mechanism that involves the formation of virus-associated pyramids (VAPs) on the host cell surface. At the end of the infection cycle, these structures open outward and create apertures through which mature virions escape from the cell. Here we describe in detail the structure and composition of VAPs formed by the Sulfolobus islandicus rod-shaped virus 2 (SIRV2) in cells of its hyperthermophilic archaeal host. We show that the VAPs are stable and autonomous assemblies that can be isolated from membranes of infected cells and purified without affecting their structure. The purified VAPs are heterogeneous in size, reflecting the dynamics of VAP development in a population of infected cells; however, they have a uniform geometry, consisting of seven isosceles triangular faces forming a baseless pyramid. Biochemical and immunoelectron microscopy analyses revealed that the 10-kDa P98 protein encoded by the SIRV2 virus is the sole component of the VAPs. The VAPs were produced in Sulfolobus acidocaldarius and Escherichia coli by heterologous expression of the SIRV2-P98 gene. The results confirm that P98 is the only constituent of the VAPs and demonstrate that no other viral protein is involved in the assembly of pyramids. P98 was able to produce stable structures under conditions ranging from moderate to extremely high temperatures (80 °C) and from neutral to extremely acidic pH (pH 2), demonstrating another remarkable property of this exceptional viral protein.